Crossing Cultures : German, Italian and French cross-cultural references - Jean-Michel Guy
The Crossing Cultures study takes an intercultural approach to the analysis of common and mutual cultural references shared by the German, Italian and French people in areas such as architectural, historical, literary, cinematographic, theatrical and musical heritage, as well as popular cultural references or figures. Polling 4,500 people across the three countries, this survey is original in scope and content: it seeks to survey the common foundation of cultures within Europe, the foundation of a European culture or of the European identity through culture. The results confirm a correlation between knowledge and educational level, and also highlight the per- sistence of national stereotypes and the lack of any genuine common culture. Nevertheless, the existence of several very widely shared transnational references demonstrates that interculturality, which presupposes a knowledge of other peoples, is not entirely out of reach. The study encourages us to reassess the aims, methods and tools of European interculturality.